2011
DOI: 10.1016/j.jep.2010.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effects of isoquercitrin and extracts from Tropaeolum majus L.: Evidence for the inhibition of angiotensin converting enzyme

Abstract: Our results show that the hypotensive effects caused by the HETM, as well as by its TMLR, may be associated with the high levels of the flavonoid ISQ found in this plant. In addition, ISQ-induced hypotension in rats is an event dependent on the inhibition of angiotensin II generation by ACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(65 citation statements)
references
References 45 publications
1
58
0
2
Order By: Relevance
“…Many studies have evaluated their antihypertensive effects under in vitro conditions. The mechanisms of actions of flavonoids include functioning as ACE inhibitors 18 , antioxidant activity and vasorelaxation 19 . In the current study, 0.5 g of APE kgG 1 of body weight, was incorporated as the daily dose which contained 25 mg of total polyphenols where the majority (around 20 mg) were flavonoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have evaluated their antihypertensive effects under in vitro conditions. The mechanisms of actions of flavonoids include functioning as ACE inhibitors 18 , antioxidant activity and vasorelaxation 19 . In the current study, 0.5 g of APE kgG 1 of body weight, was incorporated as the daily dose which contained 25 mg of total polyphenols where the majority (around 20 mg) were flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…There are different plant extracts examined on the hypotensive effects. Traditional herbal extracts 18 , blueberry 22 , cocoa 20 , purple corn, purple sweet potato and red radish 19 are some examples. A Brazilian folk medicine Cecropia glaziovii Sneth has reduced the mean systolic blood pressure by 20 mm Hg after 2 weeks of treatments where the single dose treatments of the extracts had not exerted any difference 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Isoquercitrin, also known as quercetin-3-glucoside, is a glucose-bound derivative of quercetin that is commonly found in medicinal herbs, fruits, vegetables, and plant-derived foods and beverages [10][11][12][13][14]. In recent studies, isoquercitrin has been reported to possess anti-Mayaro virus, anti-inflammatory, anti-oxidative, anti-allergic, anti-hypertensive, anti-hyperglycemic, and saluretic/diuretic effects [15][16][17][18][19][20][21][22][23]. Although the antioxidative and neuroprotective effects of isoquercitrin have been established, whether isoquercitrin could exert an anti-apoptotic effect on endothelial cells is not clear.…”
Section: Molecules2016 21 360mentioning
confidence: 99%
“…In recent studies, isoquercitrin has been reported to possess anti-Mayaro virus, anti-inflammatory, anti-oxidative, anti-allergic, anti-hypertensive, anti-hyperglycemic, and saluretic/diuretic effects [15][16][17][18][19][20][21][22][23]. Although the antioxidative and neuroprotective effects of isoquercitrin have been established, whether isoquercitrin could exert an anti-apoptotic effect on endothelial cells is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…폴리페놀의 일 종인 quercetin (QU)은 양파의 껍질 [2], 구절초 [3], 사과 과피 [4], 참가 시나무 [5] 등에 존재하는 것으로 알려져 있다. QU의 배당체인 isoquercitrin (IQ)은 항산화 [6], 항염증 [7], 항고혈압성 [8] 작용과 항알 러지 [9], 항암작용 [10] 등 다양한 약리효과가 있으나, 그의 연구가 제 한적이었다. 그 이유는 천연에서의 IQ의 존재량이 매우 적을 뿐만 아 니라 다양한 불순물의 존재 때문에 추출하는 것이 매우 어렵기 때문 이다 [11].…”
Section: )unclassified